2014
DOI: 10.1155/2014/403970
|View full text |Cite
|
Sign up to set email alerts
|

Roles of 5-Lipoxygenase and Cysteinyl-Leukotriene Type 1 Receptors in the Hematological Response to Allergen Challenge and Its Prevention by Diethylcarbamazine in a Murine Model of Asthma

Abstract: Diethylcarbamazine (DEC), which blocks leukotriene production, abolishes the challenge-induced increase in eosinopoiesis in bone-marrow from ovalbumin- (OVA-) sensitized mice, suggesting that 5-lipoxygenase (5-LO) products contribute to the hematological responses in experimental asthma models. We explored the relationship between 5-LO, central and peripheral eosinophilia, and effectiveness of DEC, using PAS or BALB/c mice and 5-LO-deficient mutants. We quantified eosinophil numbers in freshly harvested or cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Previous studies have revealed that, in addition to infections caused by bacteria, viruses, and mycoplasma, environmental and genetic factors also play an important role in pathogenesis (Masid-de-Brito et al, 2014;Namjou et al, 2014;Martineau et al, 2015). Airway obstruction caused by bronchial asthma is reversible, while airway hyper-responsiveness and stimulation caused by inflammatory mediators are characteristic of bronchial asthma (Schoepf and Heun, 2014;Lozano et al, 2014;Gadhe, 2015;López-Expósito et al, 2015;Turner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that, in addition to infections caused by bacteria, viruses, and mycoplasma, environmental and genetic factors also play an important role in pathogenesis (Masid-de-Brito et al, 2014;Namjou et al, 2014;Martineau et al, 2015). Airway obstruction caused by bronchial asthma is reversible, while airway hyper-responsiveness and stimulation caused by inflammatory mediators are characteristic of bronchial asthma (Schoepf and Heun, 2014;Lozano et al, 2014;Gadhe, 2015;López-Expósito et al, 2015;Turner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DEC to reduce murine lung inflammation was found largely dependent on 5-lipooxygenase inhibition and leukotriene products [12,33]. Furthermore, leukotrienes have been found very essential as inflammatory mediators in mediating HFD induced insulin resistance [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, leukotriene inhibitors could reduce the levels of TNF-α, IL-6 and MCP-1. The inhibition of leukotriene production was linked to the reduced COX activity since DEC has been known as an inhibitor for AA metabolism which leads to both 5-LO and COX pathways [33].…”
Section: Discussionmentioning
confidence: 99%
“…We had previously characterized (Jones et al ., ; Gaspar‐Elsas et al ., ; Queto et al ., ) a proapoptotic mechanism for regulation of eosinophil production, dependent upon iNOS and the ligand for CD95/Fas (CD95L/FasL), which operates in vivo during airway allergen challenge of sensitized mice, and accounts for the therapeutic effect of diethylcarbamazine (DEC), a leukotriene synthesis inhibitor (Matthews and Murphy, ), in experimental asthma (Queto et al ., ). Although activation of this mechanism by DEC and other drugs (de Luca et al ., ) prevents the induction of eosinophilia by allergen (Masid‐de‐Brito et al ., ), its blockade by LTD 4 and non‐steroidal anti‐inflammatory drugs (NSAIDs) (Xavier‐Elsas et al ., ) protects developing eosinophils from apoptosis. Furthermore, dexamethasone protects developing eosinophils from apoptosis by preventing expression of iNOS (de Luca et al ., ).…”
Section: Introductionmentioning
confidence: 99%